2009
DOI: 10.1007/s00244-009-9397-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Application of a Method for the Determination of Total Chromium in Rat Tissues by Inductively Coupled Plasma Mass Spectrometry

Abstract: The validation of a method for the determination of chromium (Cr) in F-344/N rat tissues by inductively coupled plasma-mass spectrometry is described. Samples were analyzed after a rapid, open-vessel microwave digestion procedure. Performance of the method was evaluated using kidney tissue across a concentration range of 0.50-5.00 microg Cr/g tissue. Data for method linearity, accuracy, precision, digest stability, and storage stability are presented along with limits of detection and quantitation data. Data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The sample preparation and analysis procedures used to determine the concentration of chromium in tissues (Levine et al, 2010) and excreta (Levine et al, 2009) in support of this investigation are presented in detail elsewhere and are summarized here. Neither of these procedures could differentiate between chromium oxidation states, so data reported are for total chromium, irrespective of oxidation state administered.…”
Section: Analysis Of Total Chromium In Tissues and Excretamentioning
confidence: 99%
“…The sample preparation and analysis procedures used to determine the concentration of chromium in tissues (Levine et al, 2010) and excreta (Levine et al, 2009) in support of this investigation are presented in detail elsewhere and are summarized here. Neither of these procedures could differentiate between chromium oxidation states, so data reported are for total chromium, irrespective of oxidation state administered.…”
Section: Analysis Of Total Chromium In Tissues and Excretamentioning
confidence: 99%
“…In response to the CrVI nomination, NTP conducted short-term and long-term toxicity and carcinogenicity studies on sodium dichromate dihydrate, a compound that contains hexavalent chromium. NTP’s products on CrVI included one toxicity report (TOX 72) ( Bucher 2007 ), one technical report (TR 546) ( NTP 2008 ), and five journal articles ( Figure 2 ) ( Collins et al 2010 ; Levine et al 2009 , 2010 ; Stout et al 2009 ; Witt et al 2013 ). TOX 72 described NTP’s 3-month studies of CrVI in drinking water in rodents and concluded that sodium dichromate dihydrate caused hyperplasia and ulceration of the stomach in rats, and anemia and lesions of the small intestine in rats and mice.…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate outcomes, or citation metrics of NTP publications (reports and journal articles), were used as a metric of informing science in stakeholder groups. For NTP journal articles ( Collins et al 2010 ; Levine et al 2009 , 2010 ; Stout et al 2009 ; Witt et al 2013 ) citations in other journal articles (reviews, original research articles, and meta analysis) and book chapters were obtained from Web of Science ( Thomson Reuters 2016 ) and Scopus (2016) , which are online, subscription-based, scientific citation indexing services, through October 2014. NTP technical reports and toxicity reports are not fully indexed in Web of Science or Scopus.…”
Section: Methodsmentioning
confidence: 99%
“…A number of sensitive techniques have been employed to detect Cr such as spectrophotometry, [6][7][8][9][10] spectrofluorimetry, 11 chemiluminescence, [12][13][14][15][16][17][18][19] plasma mass spectrometry, [20][21][22][23][24][25][26][27] and atomic adsorption spectrophotometry. 28 In comparison with these methods, electrochemical detection shows good selectivity, low cost and easy operation.…”
Section: Introductionmentioning
confidence: 99%